Pengaruh Art Therapy terhadap Kualitas Hidup Anak Kanker yang Menjalani Kemoterapi - Hidayatul Hasni; Mira Andika; Armein Syahid (Jurnal Kesehatan Andalas, 2022)
Continuous chemotherapy causes side effects in children, one of which affects the quality of life of children. The quality of life of children with cancer can be improved by providing complementary and alternative therapies, one of which is art therapy. Objective: To determine art therapy's effect on the quality of life of cancer children undergoing chemotherapy. Methods: The design of this study was a quasi-experimental one-group pre-test post-test on 30 children with cancer who underwent chemotherapy. The art therapy in this study was coloring activities. Quality of life assessed using PedsQoL instruments (Pediatric‘s Quality of Life) Generic 4.0. Data analysis used the Mann-Whitney test. Results: The average age of children with cancer was ten, and more than half (53.3%) were male. Most of them were diagnosed with Acute Leukemia Limfoblastic and more than half (73.3%) were diagnosed more than six months. There was a difference in the quality of life of children with cancer before and after being given art therapy with a p-value = 0.000 (<0.05). Art therapy affected the quality of life of cancer children undergoing chemotherapy with a p-value of 0.000 (<0.05). Conclusion: Art therapy can improve the quality of life of cancer children undergoing chemotherapy. Keywords:  art therapy, chemotherapy, children with cancer, quality of life